2023
DOI: 10.1186/s12887-023-03918-1
|View full text |Cite|
|
Sign up to set email alerts
|

Moral distress among neonatologists working in neonatal intensive care units in Greece: a qualitative study

Abstract: Background Working as a neonatologist in a neonatal intensive care unit (NICU) is stressful and involves ethically challenging situations. These situations may cause neonatologists to experience high levels of moral distress, especially in the context of caring for extremely premature infants (EPIs). In Greece, moral distress among neonatologists working in NICUs remains understudied and warrants further exploration. Methods This prospective qualit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is true that "parents are generally not informed about the evidence regarding the quality of life of surviving infants" [44]. Note, however, that the quality of life of a premature infant hospitalized in the NICU can hardly be conceived without vagueness [45]. Furthermore, Saigal et al concluded that "at young adulthood, health-related quality of life was not related to size at birth or to the presence of disability" [46].…”
Section: Interpersonal Dimensionmentioning
confidence: 99%
“…It is true that "parents are generally not informed about the evidence regarding the quality of life of surviving infants" [44]. Note, however, that the quality of life of a premature infant hospitalized in the NICU can hardly be conceived without vagueness [45]. Furthermore, Saigal et al concluded that "at young adulthood, health-related quality of life was not related to size at birth or to the presence of disability" [46].…”
Section: Interpersonal Dimensionmentioning
confidence: 99%
“…Provider uncertainty in the NICU is a prevalent aspect of the healthcare environment. Prognostic uncertainty emerged as a key factor associated with moral distress among neonatologists in a prospective qualitative study conducted to study moral distress among neonatologists working in a NICU [8]. By understanding the intricacies of uncertainty, researchers, healthcare providers, and support systems can develop tailored interventions, resources, and strategies to help individuals navigate uncertainty more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors omitted to include the funder in the Funding statement. The online version of this article has been updated to reflect the correct declarations.…”
mentioning
confidence: 99%